Data Visualization Using Rational Trigonometric Spline - Bashir, Uzma; Md. Ali, Jamaludin (Hindawi Publishing Corporation, 2013)
This paper describes the use of trigonometric spline to visualize the given planar data. The goal of this work is to determine the smoothest possible curve that passes through its data points while simultaneously satisfying the shape preserving features of the data. Positive, monotone, and constrained curve interpolating schemes, by using a